SENTIMENT ANALYSIS OF PUBLIC OPINIONS TOWARDS TELKOM UNIVERSITY POST PANDEMIC - Anindya Prameswari Putri Djakaria; Oktariani Nurul Pratiwi; Hanif Fakhrurroja (STMIK Royal, 2023)
Abstract: Twitter, as a social media platform, has rapidly grown as a means for people to express their opinions and thoughts on various topics, including education. The number of Twitter users surged to 10.645.000 in 2020, with a significant increase during the pandemic. Telkom University, as a private institution of higher education in Indonesia, has become one of the topics of discussion on Twitter. Users’ opinions about Telkom University vary, ranging from positive to negative. To gain deeper insights into public view, sentiment analysis is essential. The analysis follows the Knowledge Discovery in Databases (KDD) process, utilizing the Naive Bayes classification algorithm. The evaluation results indicate the best accuracy achieved with an 80:20 data split, resulting in an accuracy rate of 82.05%, precision of 82.3%, recall of 82.05%, and F1-Score of 82.08%. The Naïve Bayes model demonstrates good performance for sentiment analysis of public views regarding Telkom University on Twitter. Keywords: naïve bayes; sentiment analysis; twitter; telkom university. Abstrak: Media sosial Twitter berkembang pesat sebagai sarana masyarakat berekspresi untuk menuangkan opini dan pikiran mereka mengenai topik apapun, termasuk pendidikan. Pengguna Twitter meningkat tajam hingga 10.645.00 pengguna pada tahun 2020 dan terus meningkat selama pandemi. Telkom University sebagai perguruan tinggi menjadi salah satu topik yang dibicarakan yang berkaitan dengan pendidikan. Pendapat mengenai Telkom University yang diungkapkan oleh pengguna Twitter beragam, baik positif maupun negatif. Analisis sentimen diperlukan untuk memahami pandangan publik lebih mendalam. Digunakan tahapan Knowledge Discovery in Databases dan algoritma klasifikasi Naïve Bayes dalam analisis ini. Hasil evaluasi menunjukkan akurasi paling baik dicapai dengan rasio data 80:20, dengan nilai akurasi sebesar 82.05%, nilai presisi sebesar 82.3%, nilai recall sebesar 82.05%, dan nilai F1-Score sebesar 82.08%. Model klasifikasi Naïve Bayes memiliki performa baik untuk analisis sentimen pandangan publik di Twitter mengenai Telkom University. Kata kunci: analisis sentimen; naïve bayes; twitter; telkom university.